Peran Disiplin Kerja dalam Meningkatkan Kinerja Pegawai: (The Role of Work Discipline to Improve Employee Performance) - Rina Masruroh; Munir Nur Komarudin; Wely Hadi Gunawan; Iskandar Iskandar; Hepi Novita Dewi (UPT Penerbitan Universitas Jember, 2023)
This research aims to examine the role of work discipline as an intervening variable on the effect of relward and punishment on employee performance. Respondents in this research were BUMD employees in Kuningan Regency as 60 people. Analysis in research used path analysis which is used to examine the indirect effect of relward and punishment on employee performance through work discipline as an intelligence variable by using the Statistical Program for Social Sciences (SPSS) version 23. This research instrument was in the form of a questionnaire which contained statements and was distributed directly to the respondents. The research results show that (1) Rewards have a positive and significant effect on employee performance, (2) Punishment has a positive and significant effect on employee performance, (3) Reward has a positive and significant effect on work discipline, (4) Punishment has a positive and significant effect on work discipline, (5) Work discipline has a positive and significant effect on employee performance, (6) work discipline mediates the effect of reward on performance but work discipline does not mediate the effect of punishment on employee performance